Variability of the frequency spectrum of a pulse signal under exposure to optical radiation - Boronoev, V. V; Ompokov, V. D; Pupysheva, N. V; Naguslaeva, I. V (SPIE, 2021)
Some features of the frequency spectrum of the human pulse dynamics were revealed when the subject was exposed to light of different wavelengths. It has been shown that in the phase of stimulation by light, in contrast to the initial state, preferred or rejected colors cause contrasting changes in the functional state of the internal organs, either stimulating or relaxing them. The dependence of the photostimuli effect on the state and typology of the examined subjects have been detected. The obtained results can be useful for the development of technologies for managing the psychophysiological state of people.